2009
DOI: 10.1093/nar/gkn655
|View full text |Cite
|
Sign up to set email alerts
|

PhytAMP: a database dedicated to antimicrobial plant peptides

Abstract: Plants produce small cysteine-rich antimicrobial peptides as an innate defense against pathogens. Based on amino acid sequence homology, these peptides were classified mostly as α-defensins, thionins, lipid transfer proteins, cyclotides, snakins and hevein-like. Although many antimicrobial plant peptides are now well characterized, much information is still missing or is unavailable to potential users. The compilation of such information in one centralized resource, such as a database would therefore facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
167
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(170 citation statements)
references
References 18 publications
0
167
0
3
Order By: Relevance
“…A comprehensive database on AMPs with information on their activity would facilitate the study of peptide potential, enabling and promoting sequence-specificity and sequence-activity studies (Hammami et al 2009;Thomas et al 2010). Although many AMPs are now well characterized, much information is still missing or scattered over scientific literature, ie its collection and analysis is troublesome and implies time consuming manual curation.…”
Section: Information Storage and Searchmentioning
confidence: 99%
“…A comprehensive database on AMPs with information on their activity would facilitate the study of peptide potential, enabling and promoting sequence-specificity and sequence-activity studies (Hammami et al 2009;Thomas et al 2010). Although many AMPs are now well characterized, much information is still missing or scattered over scientific literature, ie its collection and analysis is troublesome and implies time consuming manual curation.…”
Section: Information Storage and Searchmentioning
confidence: 99%
“…Reinforcing this suggestion, theoretical analysis of the peptide showed that it had the potential to adopt -helical structure with a high level of amphiphilicity, indicative of an ability to interact with membranes [31,32]. This molecular architecture is adopted by many other AMPs [13,24,25] and in particular, buforin IIb, which is an -helical CAMP that crosses target membranes to bind DNA and thereby promote anticancer action via the induction of apoptosis [33]. Cr-ACP1 showed similarities to the anticancer action of buforin IIb and was found to have a strong affinity for DNA, which appeared to involve the ability of its charged and polar residues to form a stable hydrogen bond network with DNA nucleotides (Fig.…”
Section: Please Provide Corresponding Author(s) Photograph Size Shoulmentioning
confidence: 83%
“…These peptides are listed in various databases and are now known to be ubiquitous in plants [13,24,25,[44][45][46] [36] and shows molecular dynamic simulations for the interaction of Cn-AMP2 with a model cancer cell membrane. In this simulation, Cn-AMP2 (TESYFVFSVGM [106]) is in an extended conformation and approaches the surface of the membrane (Fig.…”
Section: Ahdps From Cyclotidesmentioning
confidence: 99%
See 2 more Smart Citations